2015
DOI: 10.1007/s40095-015-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of a solar combined cycle: organic Rankine cycle and absorption cooling system

Abstract: In this paper, exergy analysis is used to evaluate the performance of a combined cycle: organic Rankine cycle (ORC) and absorption cooling system (ACS) using LiBr-H 2 O, powered by a solar field with linear concentrators. The goal of this work is to design the cogeneration system able to supply electricity and ambient cooling of an academic building and to find solutions to improve the performance of the global system. Solar ACS is combined with the ORC system-its coefficient of performance depends on the inle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…The next step is the literature studies with the use of ETC in cogeneration systems. Grosu et al designed a system with ORC and absorption chiller for power and cooling production. They found that the use of 174 m 2 of collecting is able to produce about 5 kW of electricity and 46 kW of cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The next step is the literature studies with the use of ETC in cogeneration systems. Grosu et al designed a system with ORC and absorption chiller for power and cooling production. They found that the use of 174 m 2 of collecting is able to produce about 5 kW of electricity and 46 kW of cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Calise et al studied an ORC‐integrated double‐stage absorption chiller. Grosu et al developed an ORC and ARC combined system for a building. Sun et al proposed an ORC cycle integrated with ARC to utilize the waste heat of flue gas and investigated the effects of evaporation temperature ( T e ), condensation temperature ( T c ) and degree of superheat on the performance of the whole system.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a reference book deals essentially with the handling of the solar intensity fluctuations on an automatism point of view, on the basis of constant output temperature for the control of large‐scale steam turbines, with or without thermal storage. Since then, it has been shown, by the use of exergy approach that constant output temperature is not optimal, either for steam plants or other plants . The latest references present exergy optimizations of solar plants based on the available exergy flow only.…”
Section: Introductionmentioning
confidence: 99%